What is true in the Qur’anic readings and is not true in the Arabic rules "A grammatical explanatory study" The meanings of the readings of Al-Azhari "model" - Al-khawadah, Mohammad (Jordan Journal of Islamic Studies, 2023)
This study deals with the Qur’anic readings that were correct and fulfilled the rules of sound reading, but it violated the linguistic rules and the study aims to clarify and extrapolate the positions of the people of the language from the readings that violated their rules and how they deal with it. Correct readings that violate grammatical rules; Because he was distinguished by his comprehension of reading and the rule together, and his defense of the readings that were weakened by the grammarians in his book The Meanings of the Recitation